PEMBUATAN BOILER DAN TUNGKU PADA PENYULINGAN MINYAK SERAI DI DUSUN NGERIMPAK, TEMANGGUNG - Thomas Aquino Bambang Irawan; Padmawati Mangunwisastro; Mumpuni Asih Pratiwi (ABDIMAS UNWAHAS, 2018)
Ngerimpak is located in the Lowungu village, Temanggung District. The area that has the potential for the development of citronella and patchouli. In general, citronella oil and patchouli oil produced by steam distillation (steam distillation method) using the boiler, furnace, cooler and distillation equipment. Argomartani farmers need a touch of technology because their production of the citronella and patchouli oil has a small yield. With the touch of technology will improve the villagers' economy and fostering the entrepreneurial spirit. The boiler is a very important tool for generating citronella and patchouli oil in good quality according to standard trading. The the boiler we made is a type of water tube boiler with many pamphlets therein in order to improve the efficiency and fuel savings energy. The boiler also equipped with a manometer, safety valve and control level to maintain security, with the use of wood fuel.Keywords: boiler, increase efficiency, savety valve,wood